1997
DOI: 10.1046/j.1468-2982.1997.1704518.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Microscope Studies on the Effects of Neurokinin Agonists and Calcitonin Gene-Related Peptide on Dural Vessel Diameter in the Anaesthetized Rat

Abstract: This study describes a novel intravital microscope technique for direct measurement of dural blood vessel diameter through a closed cranial window in anaesthetized rats. This technique avoids removal of the skull, which can lead to problems of altered vessel reactivity and brain swelling that are encountered with open cranial window techniques. Substance P and calcitonin gene-related (CGRP) evoked increases in dural vessel diameter, which were abolished by the NK1 receptor antagonist, RP67580 and the CGRP rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
173
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(177 citation statements)
references
References 21 publications
1
173
0
3
Order By: Relevance
“…CGRP receptors have been functionally located on intracranial arterial blood vessels, where they induce vasodilatation and increases in intracranial blood flow Brian et al, 1996;Williamson et al, 1997). CGRP receptors may also be located on primary afferents, because they have been demonstrated in cultured dorsal root ganglion cells using nanogoldlinked CGRP (Segond et al, 2002).…”
Section: Cgrp Receptor Location and Possible Sites Of Actionmentioning
confidence: 99%
“…CGRP receptors have been functionally located on intracranial arterial blood vessels, where they induce vasodilatation and increases in intracranial blood flow Brian et al, 1996;Williamson et al, 1997). CGRP receptors may also be located on primary afferents, because they have been demonstrated in cultured dorsal root ganglion cells using nanogoldlinked CGRP (Segond et al, 2002).…”
Section: Cgrp Receptor Location and Possible Sites Of Actionmentioning
confidence: 99%
“…, and this has been shown previously to produce a maximal dilation (Williamson et al, 1997a). In those preparations where capsaicin was used to dilate the dural blood vessels, capsaicin was given as an intravenous bolus up to 7 g kg Ϫ1 , until a maximal dilation was observed (Akerman et al, 2003b).…”
mentioning
confidence: 92%
“…Neurogenic dural vasodilation identifies potential migraine targets such as sumatriptan (Williamson et al, 1997b) and opioid agonists (Williamson et al, 2001). CGRP injections trigger both migraine (Lassen et al, 2002) and dural vessel dilation (Williamson et al, 1997a) and CGRP antagonists have acute antimigraine properties (Olesen et al, 2003). NO is another known trigger of migraine (Dalsgaard-Nielsen, 1955;Thomsen et al, 1994) and dural vessel dilation (Akerman et al, 2002c).…”
mentioning
confidence: 99%
“…Williamson et al (1997a) demonstrated that electrical stimulation of dura mater causes CGRP release from the prejunctional nerve fibers innervating the dural blood vessels, resulting in reproducible vasodilation. Blocking this vasodilation has proved to be an effective indicator of acute antimigraine efficacy, with many compounds, including the triptans (Williamson et al, 1997b,c) and CGRP antagonists (Williamson et al, 1997a), able to inhibit the vasodilation as well as provide effective antimigraine therapy Olesen et al, 2004).…”
mentioning
confidence: 99%